How underdog barks the loudest : Supporting female micro-entrepreneurship in Sub-Saharan Africa - Ylinen, Nelli (My University, 2024)
Entrepreneurship is widely recognized as a driving force for social change. Not only because it creates added value to society but recently also because entrepreneurship can serve as a way of demarginalization for individuals confronting societal or environmental challenges. Researchers argue that the experience of being an underdog can advance the development of invaluable human capital, including self-efficacy, risk tolerance, resilience, and creativity, all of which are essential for entrepreneurial success. In Sub-Saharan Africa, a significant proportion of adult females engage in entrepreneurship, primarily as micro-entrepreneurs and often due to limited alternative opportunities. However, the entrepreneurial environment in the region is challenging due to a variety of factors, necessitating support and equal access to different resources in order to establish successful and sustainable businesses. Historical legacies, notably colonialism, and future projections, including rapid population growth, highlight the imperative for international stakeholders to act towards sustainable development of the African continent. This study aims to investigate female micro-entrepreneurship in Sub-Saharan Africa and propose strategies for its support. The main research question guiding this thesis is: How could female micro-entrepreneurship in Sub-Saharan Africa be supported? Employing a qualitative research approach, the empirical data was collected through semi-structured interviews with nine female micro-entrepreneurs in Namibia, representing various business sectors. Additionally, observations of the entrepreneurial environment in Namibia were conducted, including photographic documentation illustrating the nature of selected business activities. The findings of the empirical data underscore the diversity of female micro-entrepreneurship and the unique creativity and persistence demonstrated by women navigating their circumstances. The theoretical contributions confirm previous academic research on female entrepreneurship in Sub-Saharan Africa, highlighting the importance of context and showing that especially institutional voids, resource scarcities, family responsibilities and trust issues create barriers to business. The findings further follow the Challenge-based entrepreneurship and bricolage -theories by noting that with persistence, hard-working mentality, family support and creativity female micro-entrepreneurs can turn challenging environments into opportunities and success. A novel finding of this study is that while many female micro-entrepreneurs may initiate businesses out of necessity, most of them exhibit strong opportunity-driven entrepreneurial ambitions. The aim of this study was achieved by formulating practical implications for supporting female entrepreneurship in Sub-Saharan Africa. These suggestions include the enrichment of intangible resources such as business skills, networking opportunities, and entrepreneurial self-esteem, alongside providing direct assistance, including essential equipment or financial support. Effective implementation of these strategies requires careful research and planning to identify suitable support recipients and actions and to avoid misallocation of resources. Moreover, it is essential to notice female entrepreneurs as innovative specialists within their unique contexts, already endowed with many characteristics that foster entrepreneurial success.

Yrittäjyys tunnetaan laajalti yhteiskunnallisen muutoksen liikkeellepanevana voimana. Ei pelkästään siksi, että se luo yhteisöllistä lisäarvoa, vaan myös siksi, että sen kautta yhteiskunnallisia ja ympäristöllisiä haasteita kohtaavat ihmiset voivat saavuttaa paremman elintason. Tutkijoiden mukaan altavastaajana olemisen kokemus voi edistää aineettoman pääoman, kuten oma-aloitteisuuden, riskinsietokyvyn ja luovuuden kehittymistä, jotka kaikki ovat välttämättömiä ominaisuuksia menestyvälle yrittäjälle. Saharan eteläpuolisessa Afrikassa merkittävä osa aikuisesta naisväestöstä harjoittaa yrittäjyyttä pääasiassa mikroyrittäjänä ja usein siksi, että tarjolla ei ole paljolti muita mahdollisuuksia. Alueen yrittäjyysympäristö on kuitenkin useiden tekijöiden seurauksena haastava, edellyttäen tukea ja tasavertaista pääsyä resursseihin menestyvien ja kestävien yritysten perustamiseksi. Afrikan synkkä historia, erityisesti kolonialismi, ja tulevaisuuden ennusteet, kuten nopea väestönkasvu, korostavat kansainvälisten sidosryhmien vastuuta ja välttämättömiä toimia kohti mantereen kestävää kehitystä. Tämän tutkielman tavoitteena on tutkia Saharan eteläpuolisen Afrikan naismikroyrittäjyyttä ja ehdottaa menetelmiä sen tukemiseksi. Tutkielmaa ohjaava pääkysymys on: Miten Saharan eteläpuolisen Afrikan naismikroyrittäjyyttä voitaisiin tukea? Tutkimuksen empiirinen aineisto kerättiin kvalitatiivista tutkimusta hyödyntäen haastatteluina, joihin valittiin mukaan yhdeksän namibialaista naismikroyrittäjää, kaikki edustaen eri toimialoja. Lisäksi tehtiin havaintoja Namibian yrittäjyysympäristöstä, sisältäen esimerkiksi valokuvadokumentaation, joka havainnollistaa valikoitujen yritysten toimintaa ja liikeympäristöä. Empiirisen aineiston havainnot korostavat naisyrittäjyyden monimuotoisuutta sekä uniikkia luovuutta ja sinnikkyyttä, jota yrittäjät osoittavat selvitäkseen liiketoimintaympäristössään. Teoreettiset kontribuutiot vahvistavat aiempaa akateemista tutkimusta naisyrittäjyydestä Saharan eteläpuolisessa Afrikassa, korostaen kontekstin merkitystä ja osoittaen, että erityisesti institutionaaliset tekijät, resurssien niukkuus, perhevastuut ja luottamuskysymykset luovat esteitä liiketoiminnalle. Tulokset seuraavat myös ”haastepohjaista yrittäjyysteoriaa” toteamalla, että sinnikkyydellä, ahkeralla mentaliteetilla, perheen tuella ja luovuudella altavastaajan asemassa olevat naismikroyrittäjät voivat vaikuttaa haastavaan ympäristöönsä ja myös hyödyntää haasteita menestyksen saavuttamiseksi. Eräs tutkimuksen löytö selventää, että vaikka monien naismikroyrittäjien alkuperäinen motivaatio liiketoiminnalle on pakko, suurimmalla osalla heistä on silti vahvoja tavoitteita yrityksen kasvun ja tulevaisuuden suhteen. Tutkimuksen tavoite saavutettiin muodostamalla käytännön suosituksia naismikroyrittäjien tukemiselle Saharan eteläpuolisessa Afrikassa. Suosituksiin kuuluvat aineettomien resurssien, kuten liiketoimintataitojen, verkostoitumismahdollisuuksien ja liiketoiminnallisen itsetunnon edistäminen. Myös suoran aineellisen avun antaminen välttämättömien tarvikkeiden ja taloudellisen tuen kautta nähtiin vaihtoehtoina. Näiden strategioiden tehokas toteuttaminen edellyttää kuitenkin huolellista tutkimusta ja suunnittelua sopivien tuen saajien ja toimien tunnistamiseksi ja resurssien väärin kohdistamisen välttämiseksi. Lisäksi on tärkeää huomioida naisyrittäjät innovatiivisina oman ympäristönsä asiantuntijoina, joilla on jo valmiiksi monia yrittäjyyttä edistäviä ominaisuuksia ja vahvuuksia.
Keywords: entrepreneurship, entrepreneurial ecosystem, female micro-entrepreneurship, challenge-based entrepreneurship, bricolage, Sub-Saharan Africa, sustainable development, support